2011
DOI: 10.1186/1475-2891-10-79
|View full text |Cite
|
Sign up to set email alerts
|

Dietary availability patterns of the brazilian macro-regions

Abstract: IntroductionEpidemiological studies have raised concerns about the role of dietary patterns on the risk of chronic diseases and also in the formulation of better informed nutrition policies.ObjectiveThe development of a dietary availability patterns according to geographic regions in Brazil.MethodologyThe 2002-2003 Brazilian Household Budget Survey was conducted in 48,470 households. Dietary availability patterns were identified by Principal Component Analysis using as a unit of analysis the survey's Primary S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
50
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 19 publications
7
50
0
6
Order By: Relevance
“…Nascimento et al 18 with the objective of identifying dietary patterns in different Brazilian regions, used data from a nationally representative sample and observed that elderly persons in the southeast region of the country are more related to a Mixed pattern (vegetables, fruits, root vegetables, breads, cookies, dairy products, fish, butter or margarine and sugary drinks) than the other pattern found, which was named Rice and Beans. Both the Traditional pattern found in the present study and the Mixed pattern of the Brazilian population indicated the habit of the elderly of consuming vegetables (greens and vegetables).…”
Section: Discussionmentioning
confidence: 99%
“…Nascimento et al 18 with the objective of identifying dietary patterns in different Brazilian regions, used data from a nationally representative sample and observed that elderly persons in the southeast region of the country are more related to a Mixed pattern (vegetables, fruits, root vegetables, breads, cookies, dairy products, fish, butter or margarine and sugary drinks) than the other pattern found, which was named Rice and Beans. Both the Traditional pattern found in the present study and the Mixed pattern of the Brazilian population indicated the habit of the elderly of consuming vegetables (greens and vegetables).…”
Section: Discussionmentioning
confidence: 99%
“…Examining results from the Family Budget Study (children, adults and elderly individuals), a study found that the typical Brazilian pattern contains foods that were noteworthy in the dietary representation from all Brazilian regions. 66 The absence of the association with this dietary pattern and obesity was evident in our study. To the best of our knowledge, no studies have addressed this issue.…”
Section: Discussionmentioning
confidence: 49%
“…66 The comparison of this pattern with international studies is not actually feasible since this combination of rice and beans is typically Brazilian. We did not identify the association of this dietary pattern with obesity in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The north region presented higher protein-energy percentage, and also higher total energy consumption. These results reflect the regional habits of this population, characterized by the intake of fish, birds, and eggs, also sources of protein 23 . Enes and Silva 24 assessed the POF 2002-2003 data and observed that the lower the per capita family income, the lower the energy intake, and the north region was mostly influenced by the income.…”
Section: Discussionmentioning
confidence: 99%
“…In the center-west region, besides the "rice and beans" pattern, another consumption pattern was the "mixture", which contains foods such as vegetables, tubers, and fruits, but also includes cakes, cookies, butter, and margarine, thus explaining the high percentage of energy coming from lipids and higher prevalence of obesity 23 . The low EP coming from carbohydrates was associated with the higher intake of lipids, risk factor for the development of diabetes and heart disease 27 .…”
Section: Discussionmentioning
confidence: 99%